Are the young the Others in Croatian media? – An analysis of newspaper articles about violence among the young - Anita Skelin Horvat ([sic])
The media are an important tool for creating public opinion and they can influence the creation of laws and policy. Media representation of young people is important because it can influence the public image of them and it can also influence the young themselves. On the other side, young people can be discriminated against and treated with suspicion because of a specific media image of them. In this paper we analyse a corpus of newspaper articles about violence among the young that occurred in Croatia recently. Analysing this discourse we try to find out who the participants are and what they emphasise as the most important questions and issues in connection with the young and violence. We try to find out how the creation of a text is influenced by power relations and other factors connected with the media (i.e. public opinion, stereotypes, public panic) and what the main image of the young created by the media is. We also analyse how language is used and which language and discourse elements (i.e. style, metaphors, and collocations) are used in creating a specific media image of the young.